Systems engineering opportunities for agricultural and organic waste management in the food–water–energy nexus. (November 2017) - Garcia, Daniel; You, Fengqi
Highlights: Review of agricultural and organic wastes within the food–water–energy nexus (FWEN). Overview of interconnections between FWEN and waste streams. Research opportunities in process and supply chain design from a FWEN perspective. Economic and environmental considerations. Abstract : Managing food, water, and energy waste streams leads to more sustainable production, consumption, and distribution processes in the food–water–energy nexus (FWEN). Agricultural and organic waste streams within the FWEN can be difficult to manage due to both volume and their potential environmental impacts. However, they are also often characterized by a rich mix of organic compounds, ripe for conversion into energy or value-added products. Process systems engineering (PSE) stands uniquely positioned to understand the interconnections between food, water, and energy of agricultural and food wastes, wastewater, and municipal solid waste (MSW). Targeted advances in systems analysis as well as design and optimization of integrated FWEN waste management technologies and processes are expected to have the greatest impact. When building integrated mathematical models, care must be taken to consider waste treatment not as an independent process unaffected by the FWEN, but as a core component of the FWEN, connected to all nexus resources and systems.